Empathy in individuals clinically at risk for psychosis: Brain and behaviour. (November 2015) - Derntl, Birgit; Michel, Tanja Maria; Prempeh, Pamela; Backes, Volker; Finkelmeyer, Andreas; Schneider, Frank; Habel, Ute
Abstract : Background: Empathy is a basic human ability, and patients with schizophrenia show dysfunctional empathic abilities on the behavioural and neural level. Aims: These dysfunctions may precede the onset of illness; thus, it seems mandatory to examine the empathic abilities in individuals at clinical high risk for psychosis. Method: Using functional magnetic resonance imaging, we measured 15 individuals at clinical high risk of psychosis (CHR group) and compared their empathy performance with 15 healthy volunteers and 15 patients with schizophrenia. Results: Behavioural data analysis indicated no significant deficit in the CHR group. Functional data analysis revealed hyperactivation in a frontotemporoparietal network including the amygdala in the CHR group compared with the other two groups. Conclusions: Despite normal behavioural performance, the CHR group activated the neural empathy network differently and specifically showed hyperactivation in regions critical for emotion processing. This could suggest a compensatory mechanism reflecting emotional hypersensitivity or dysfunctional emotion regulation. Further investigations should clarify the role of these neural alterations for development and exacerbation of psychosis.